Optimal Colorant Composition For Agateware Products at Lukita Ceramic Studio Yogyakarta (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This article discusses the optimal dye composition for ceramic products produced using the agateware technique at Lukita Ceramic Studio. The agateware technique is known for its unique color patterns and gradations resulting from mixing various types of colored clay. This technique requires the right dye to obtain the desired aesthetic results. The purpose of this study is to identify the color composition needed to make agateware products at Lukita Ceramic Studio so that they can have quality and visual appeal. This study uses a qualitative descriptive methodology with the aim of clearly describing the steps and results of selecting the right coloring composition for agateware ceramic products made at Lukita Ceramic Studio. The results of the study show that several coloring processes, such as white, blue, and orange, and so on, produce harmonious and complex patterns and increase the aesthetic value of the product. In addition, this study examines the impact of dye composition on consumer perception and market potential. It is hoped that this will make a significant contribution to the development of innovative and high-quality agateware products at Lukita Ceramic Studio.